Genetics of host response to Leishmania tropica in mice - different control of skin pathology, chemokine reaction, and invasion into spleen and liver. - Tetyana Kobets; Helena Havelková; Igor Grekov; Valeriya Volkova; Jarmila Vojtíšková; Martina Slapničková; Iryna Kurey; Yahya Sohrabi; Milena Svobodová; Peter Demant; Marie Lipoldová (Public Library of Science (PLoS), 2012)
BACKGROUND: Leishmaniasis is a disease caused by protozoan parasites of genus Leishmania. The frequent involvement of Leishmania tropica in human leishmaniasis has been recognized only recently. Similarly as L. major, L. tropica causes cutaneous leishmaniasis in humans, but can also visceralize and cause systemic illness. The relationship between the host genotype and disease manifestations is poorly understood because there were no suitable animal models. METHODS: We studied susceptibility to L. tropica, using BALB/c-c-STS/A (CcS/Dem) recombinant congenic (RC) strains, which differ greatly in susceptibility to L. major. Mice were infected with L. tropica and skin lesions, cytokine and chemokine levels in serum, and parasite numbers in organs were measured. PRINCIPAL FINDINGS: Females of BALB/c and several RC strains developed skin lesions. In some strains parasites visceralized and were detected in spleen and liver. Importantly, the strain distribution pattern of symptoms caused by L. tropica was different from that observed after L. major infection. Moreover, sex differently influenced infection with L. tropica and L. major. L. major-infected males exhibited either higher or similar skin pathology as females, whereas L. tropica-infected females were more susceptible than males. The majority of L. tropica-infected strains exhibited increased levels of chemokines CCL2, CCL3 and CCL5. CcS-16 females, which developed the largest lesions, exhibited a unique systemic chemokine reaction, characterized by additional transient early peaks of CCL3 and CCL5, which were not present in CcS-16 males nor in any other strain. CONCLUSION: Comparison of L. tropica and L. major infections indicates that the strain patterns of response are species-specific, with different sex effects and largely different host susceptibility genes.